Judicialization In and Around the South China Sea - Kodama, Yoshinori (UI Scholars Hub, 2023)
This article examines why international legal dispute settlement procedures are traditionally less frequently resorted to in Southeast Asia, compared to other regions. It also analyzes why and how, since the beginning of this century, international legal cases, both judicial and arbitral, have been consistently used for settling maritime disputes in and around the South China Sea. Then, it presents prescriptive suggestions for further use of judicial and arbitral procedures. The method of analysis is based upon the examination and scrutiny of factual materials, including relevant international cases regarding the region, as well as interviews engaged by the author with officials and experts in the region. Universal trends and experience of judicial procedures will be deductively analyzed. The article first summarizes conditions and characteristics in the Asian region, particularly Southeast Asia, where the South China Sea is located. It, secondly, examines the factual basis for international legal cases involving the region, especially from the viewpoint as to how relevant States decided to resort to legal processes, as well as how judgments and awards affect ex post relations between parties. Finally, the article will examine more universal dimensions for the use of judicial or arbitral procedures, particularly factors and elements which encourage the State to resort to such procedures.